Technique and timing in women's inward tow and one half somersault tuck (405C) and the men's inward two and one half somersault pike (405B) 3m springboard dives - Sanders, R.; Burnett, A. (Sports Biomechanics, 2003)
The purpose of this study was to compare the inward two and one half somersault dive in a tuck position (405C) performed by females (n=22) and the inward two and one half somersault dive in a pike position (405B) performed by males (n=24) to determine changes required by females to successfully perform 405B. Key performance variables in inward dives were also compared to those of backward dives. Video data of the dives performed at the 1999 FINA World Diving Cup were captured and digitised to obtain times and postures of the divers at specific events including takeoff and entry. Estimates of flight height and mass-normalised work done on the springboard were obtained from flight times. Some females worked the springboard strongly enough to generate sufficient height and rotation to perform 405B. Males performed 405B comfortably because they achieved better height and rotation than the females. A comparison of backward and inward dives revealed that divers are able to attain greater height in backward dives than inward dives.